Reflection of mystical themes in Attar’s musical verses - BehroozNadimi; Ashrafzadeh, Reza; TaghaviBehbahani, Majid (International Journal of Psychosocial Rehabilitation, 2021)
Attar is one of the representatives of Iranian mystical poetry. In the verse of his works, he has dealt with mysticism and expressed mystical thoughts in various forms. In Attar’s poetry, like other classical poets, musical instruments and terms are mentioned. A study of Attar’s works shows that with the help of music and its terms, he has proposed and illustrated his desired themes and purposes, especially mystical themes and purposes. In this descriptive-analytical method, we studied Attar’s works (Al-Tair region, Misayatnameh, Asrarnameh, Elahinameh and Attar’s Divan) and examined those musical verses that have been dealt with from a mystical point of view. Findings showed that among the instruments, the most frequent instrument was the harp. Also, among the musical terms, "curtain" is used more than other terms. Most of the pictures that Attar made with musical instruments and terms are related to a person, his feelings and circumstances. Among the themes used, love, desire, knowledge and pain have the highest frequency.